Diverse paths to hybrid incompatibility in Arabidopsis. (17th September 2018) - Vaid, Neha; Laitinen, Roosa A. E.
Summary: One of the most essential questions of biology is to understand how different species have evolved. Hybrid incompatibility, a phenomenon in which hybrids show reduced fitness in comparison with their parents, can result in reproductive isolation and speciation. Therefore, studying hybrid incompatibility provides an entry point in understanding speciation. Hybrid incompatibilities are known throughout taxa, and the underlying mechanisms have mystified scientists since the theory of evolution by means of natural selection was introduced. In plants, it is only in recent years that the high‐throughput genetic and molecular tools have become available for the Arabidopsis genus, thus helping to shed light on the different genes and molecular and evolutionary mechanisms that underlie hybrid incompatibilities. In this review, we highlight the current knowledge of diverse mechanisms that are known to contribute to hybrid incompatibility. Significance statement: The advances of high‐throughput technologies have allowed the use of Arabidopsis hybrids not only to investigate the genetic mechanisms but also to obtain evolutionary insights on the maintenance of incompatibility alleles in nature. In this review we highlight the current knowledge of the diversity of genetic and evolutionary mechanisms known to contribute to hybrid incompatibility in Arabidopsis genus.